(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article analyzes the current state of Russia’s external public debt, as well as a comparative analysis of the debt sustainability of different countries. The reasons for the growth of the ratio of public debt to Russia’s GDP in the last few years have been revealed, despite the low level of debt load of the state and the slowdown in the growth of external borrowing. The necessity of changing the current debt policy of the state in the difficult current geopolitical conditions, accompanied by an increase in the number of economic sanctions, is noted. The directions of increasing the effectiveness of the settlement of Russia’s external debt are identified.